2010
DOI: 10.1038/labinvest.2010.153
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model of autoimmune pancreatitis with salivary gland involvement triggered by innate immunity via persistent exposure to avirulent bacteria

Abstract: The pathogenesis of autoimmune pancreatitis (AIP) remains unknown. Here, we investigated the possible involvement of chronic, persistent exposure to avirulent bacteria in the pathogenesis of AIP. C57BL/6 mice were inoculated with heatkilled Escherichia coli weekly for 8 weeks. At 1 week and up to 12 months after the final inoculation, the mice were killed to obtain samples. At 1 week after the final E. coli inoculation, marked cellular infiltration with fibrosis was observed in the exocrine pancreas. Cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 33 publications
1
35
0
1
Order By: Relevance
“…by immunization with self-antigens, injection of pathogens [35] or via adoptive transfer of autoreactive cells or T regs [36][37][38]. However, such models can be highly variable.…”
Section: Discussionmentioning
confidence: 99%
“…by immunization with self-antigens, injection of pathogens [35] or via adoptive transfer of autoreactive cells or T regs [36][37][38]. However, such models can be highly variable.…”
Section: Discussionmentioning
confidence: 99%
“…These slowly progressive steps eventually lead to the development of autoimmune diseases. Modified from previous reports (Haruta et al, 2010a; Yanagisawa et al, 2011). …”
Section: Resultsmentioning
confidence: 93%
“…The pancreas in the recipient RAG2 −/− mice showed cellular infiltration in the exocrine pancreas, especially around the pancreatic ducts, indicating that the E. coli -inoculated mouse spleen cells possess the ability to reproduce pathological alterations in the pancreas of naĂŻve mice. Similarly, when the spleen cells of donor S. intermedius -inoculated mice were transferred to RAG2 −/− mice, primary biliary cirrhosis (PBC)-like cholangitis in the liver was induced, similar to that seen in the donor (Haruta et al, 2010b). The AIP-like inflammatory region in the pancreases of recipient mice with spleen cells transferred from E. coli -inoculated mice (Haruta et al, 2010a), showed that most of the cellular infiltrates in the target organs were CD3-positive, indicating that these cells in both models originated from the donor mice.…”
Section: Commensal Bacteria-induced Mouse Model Of Aipmentioning
confidence: 91%
See 1 more Smart Citation
“…with heat-killed E. coli weekly for 8 weeks, marked cellular infiltration with fibrosis was observed in the exocrine pancreas accompanied by a high serum gamma-globulin level and the production of autoantibodies against CA-II and LF. Bacterial infection apparently triggered autoimmune pancreatitis-like pathological alterations in mice that strikingly resembled AIP in humans [61]. …”
Section: Infection-induced Mouse Model Of Aipmentioning
confidence: 99%